A NEW STRATIGRAPHY OF ISTANBUL TERTIARY DEPOSITS AND THEIR ENGINEERING PROPERTIES - Yildirim, Mustafa; Akguner, Cem; Tonaroglu, Murat; Selcuk, Murat E. (YILDIZ TECHNICAL UNIV, 2010)
For over 50 years, the Upper Oligocene - Upper Miocene sedimentary sequence in Istanbul has been thought to be composed of two distinct sequences with an unconformity in between and mapped accordingly. Based on recent field observations and borehole data, it has been concluded that the Gurpinar, eukurcesme and Gungoren Formations actually constitute a single sequence, named Avcilar Formation, since they are composed of regularly alternating clay- sand/sandstone beds and lenses. The Bakirkoy Formation, which is typically composed of carbonate rocks, conformably overlies the Avcilar Formation. Adopting this new stratigraphy eliminates the confusion in selecting suitable geotechnical and engineering geological parameters representing the formations in question and, thus, helps in preventing errors in overall interpretation of site conditions.
Keywords: Tertiary deposits; shear wave velocity; Istanbul; stratigraphy; mapping; Avcilar formation; Engineering